Staple line lockstitch reinforcement decreases clinically relevant pancreatic fistula following distal pancreatectomy: Results of a propensity score matched retrospective analysis - Tian, Feng; Luo, Ming-jie; Sun, Meng-qing; Lu, Jun; Huang, Bo-wen; Guo, Jun-chao (Frontiers in Oncology, 2022)
Background: Clinically relevant postoperative pancreatic fistula (CR-POPF) remains the primary complication of distal pancreatectomies. We aimed to review whether staple line reinforcement with continuous lockstitches would lead to decreased grade B and C pancreatic fistula in patients undergoing distal pancreatectomy. Methods: This retrospective study enrolled consecutive patients scheduled to undergo distal pancreatectomy at a large tertiary hospital. A comparison was conducted between lockstitch reinforcement and non-reinforcement for remnant closure during distal pancreatectomies from August 2016 to February 2021. Propensity score matching was applied to balance the two groups with covariates including abdominal and back pain, diabetes mellitus, and estimated blood loss. The primary outcome was CR-POPF rate. Results: A total of 153 patients were enrolled in the study (89 lockstitch reinforcements, 64 non-reinforcements), of whom 128 patients (64 per group) were analysed after propensity score matching (1:1). The total CR-POPF rate was 21.9%. CR-POPF was identified in 12.5% (8/64) of patients who underwent resection with lockstitch reinforcement and 31.2% (20/64) of patients without reinforcement (odds ratio 0.314, 95% confidence interval 0.130-0.760, P=0.010). No deaths occurred in either group. Neither the major complication rate nor the length of hospital stay after surgery differed between the groups. Conclusions: Compared with the use of stapler alone, staple line lockstitch reinforcement for stump closure during distal pancreatectomy could reduce the CR-POPF rate. Further multicenter randomized clinical trials are required to confirm these results.